Doxorubicin interactions with bovine serum albumin revealed by microdialysis with on‐line laser‐induced fluorescence detection at subpicogram level. Issue 11 (15th May 2015) - Blazkova, Iva; Smerkova, Kristyna; Blazkova, Lucie; Vaculovicova, Marketa; Stiborova, Marie; Eckschlager, Tomas; Beklova, Miroslava; Adam, Vojtech; Kizek, Rene
Abstract : Doxorubicin (DOX) is an effective antitumor drug employed for treatment of a wide range of cancers types such as neuroblastoma, osteosarcoma, breast and esophageal carcinomas. On the other hand, the cumulative dose is restricted (300–550 mg/m 2 ) and its amount administered to a patient has to be closely controlled due to its cardiotoxicity. To understand the mechanisms of the DOX side effects as well as to reveal the ways how to reduce its adverse impact on cardiomyocytes, the interactions with particular components of the blood and tissues have to be studied in greater detail. In this work, microdialysis technique was optimized to extract DOX from samples and subsequently monitor its interaction with BSA. Finally, the microdialysis probe was connected on‐line to the LIF detector to ensure the real‐time detection. The best flow rate was 1 μL/min and after 120 min of microdialysis 28% of the DOX was dialyzed out from the sample. The results from investigation of the DOX–BSA interaction indicate that the interaction occurs in less than 30 min, causing marked decrease in the amount of DOX extracted by microdialysis.